Children's Mental Models of Prenatal Development - van Schijndel, Tessa J. P.; van Es, Sara E.; Franse, Rooske K.; van Bers, Bianca M. C. W.; Raijmakers, Maartje E. J. (Frontiers in Psychology, 2018)
Children’s thinking about prenatal development requires reasoning about change that cannot be observed directly. How do children gain knowledge about this topic? Do children have mental models or is their knowledge fragmented? In Experiment 1, results of a forced-choice questionnaire about prenatal development (6- to 13-year-olds’; N = 317) indicated that children do have a variety of coherent, grade-related, theories about early shape of the fetus, but not about bodily functions. Coherence of the mental models was enhanced by a preceding generative task. Children’s mental models were in agreement with reasoning about natural transformations (Rosengren et al., 1991) and constraints in representational flexibility (Karmiloff-Smith, 1992). In Experiment 2, an open-question interview was administered (6- to 12-year-old children; N = 37). The interview resulted in grade-unrelated, incoherent responses. This study contributes to a deeper understanding of naïve biology and to the effects of different methodologies being used in the area of mental models.